(untitled) (Nigerian Journal of Technology, 2019)
Dewatered cassava mash (DCM) sieve aperture is fixed arbitrarily at 3mm by local craftsmen. This contributes to high energy and time consumption. This research focused on modifying this aperture experimentally and to assess its effect on sieving time, throughput capacity, and particle size dimension. Sieving was done with four replications using 2kg DCM across 3mm, 5mm and 7mm apertures. The result showed throughput capacity of 35kg/h, 59kg/h and 84kg/h respectively. The Anova, at 5% shows a significant difference among the means of the throughput capacity. Also, effective size D10 of garified sample, fineness modulus and average particle size of the sieves were close. The tcal for the particles from 3mm compared to 5mm and 7mm sieve were 0.61 and 1.1 respectively whereas the tcrital was 2.15 showing that the particle sizes do not differ significantly. Sieve aperture can be modified to between 5mm to 7mm inclusive with good results. http://dx.doi.org/10.4314/njt.v38i2.30